Galaxy And Mass Assembly (GAMA): Defining passive galaxy samples and searching for the UV upturn. Issue 2 (19th December 2019) - Phillipps, S; Ali, S S; Bremer, M N; De Propris, R; Sansom, A E; Cluver, M E; Alpaslan, M; Brough, S; Brown, M J I; Davies, L J M; Driver, S P; Grootes, M W; et al.
ABSTRACT: We use data from the GAMA and GALEX surveys to demonstrate that the UV upturn, an unexpected excess of ultraviolet flux from a hot stellar component, seen in the spectra of many early-type galaxies, arises from processes internal to individual galaxies with no measurable influence from the galaxies' larger environment. We first define a clean sample of passive galaxies without a significant contribution to their UV flux from low-level star formation. We confirm that galaxies with the optical colours of red sequence galaxies often have signs of residual star formation, which, without other information, would prevent a convincing demonstration of the presence of UV upturns. However, by including (NUV− u ) and WISE (W2–W3) colours, and FUV data where it exists, we can convincingly constrain samples to be composed of non-star-forming objects. Using such a sample, we examine GALEX photometry of low-redshift GAMA galaxies in a range of low-density environments, from groups to the general field, searching for UV upturns. We find a wide range of (NUV− r ) colours, entirely consistent with the range seen – and attributed to the UV upturn – in low-redshift red sequence cluster galaxies. The range of colours is independent of group multiplicity or velocity dispersion, with isolated passive galaxies just as likely to have blue UV-to-optical colours, implying significant upturn components, as those in richer groups and in the previous data on clusters. This is supported by equivalent results for (FUV− r ) colours which are clear indicators of upturn components.